VALIDITAS MEDIA TUAS PADA PEMBELAJARAN IPA MATERI PESAWAT SEDERHANA - Salafudin; Noer Af’idah (Discovery : Jurnal Ilmu Pengetahuan, 2022)
Learning media is an important part of learning activities that serves to help convey messages from various learning sources in an effective and planned manner, so that learning objectives will be achieved. But so far, teachers rarely use learning media, so they have difficulty in conveying material to students. This causes learning activities to seem boring and students often have difficulty understanding the material. This problem usually occurs in materials that require a high level of understanding, such as simple plane materials, especially the discussion of levers. This study aims to develop lever media as a learning medium for VIII grade junior high school students on simple planes. This study uses the ADDIE development method which includes the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. The feasibility of the product developed in this study was obtained from the evaluation of the validation sheet by media expert validators and material experts, namely two science education lecturers at Hasyim Asy'ari University Tebuireng Jombang, and the practitioner validator, a science teacher from SMP Negeri 1 Jombang. From the assessment of the validation sheet obtained results in the form of qualitative and quantitative data. Qualitative data in the form of suggestions and input are used as a reference to improve and revise the lever media developed. While the quantitative data is processed to get the value of the validity of the developed lever media. Based on the results of the lever media validation assessment, it was obtained an average score of 3.82 in the very good category and a validity score of 95.5% in the very valid category. Keywords​: ​​ Learning Media, Lever Media, Simple Plane